EP320/#820 'What do people really want to know about cancer BRCA prevention?' Gynecologic counselling changes BRCA patients choices?. (4th December 2022) - Picardo, Elisa; Mitidieri, Marco; Barbierato, Ilaria; Fucina, Stefano; Gemmiti, Silvia; Gervasoni, Fiammetta; Roberta, Francescato; Chiara, Benedetto; Zambelli, Alberto; Saverio, Danese
Abstract : Objectives: The purpose of this study is to emphasize the role of oncogenetic counseling in a cohort of women affected by BRCA 1/2 germline mutations. Oncological counseling is essential to ensure an appropriate interpretation of the genetic test result, explain the management possibilities, helping people in the choices of medical options. Mutations of the BRCA 1 and BRCA 2 genes increase the risk of developing familial breast and ovarian cancer. Prevention options we can offer to BRCA mutated patients are intensified surveillance, chemoprevention and prophylactic surgery regarding breast and ovarian cancer. Methods: A 35-item questionnaire on the type of prevention choice made was developed and offered to 197 BRCA mutated patients of the Sant 'Anna Hospital in Turin from September 2018 to February 2021. We selected 61 patients who correctly completed the questionnaire. Results: Concerning breast cancer risk reduction, 63% of patients tell us that the preferred option is intensified breast surveillance while for the ovary, the preferred option is surgery in 50% of patients. In both cases the variable 'desire for motherhood' influenced the patient' choices in an important way. The 90% of women were satisfied with the doctor's help in directing their choice of prevention. Conclusions: Physicians should discuss the advantages and disadvantages of risk reduction strategies with high-risk women. Concerning ovarian surgery, surgical menopause and estrogen deprivation are two aspects to consider and to inform patients about symptoms and their treatment. From the point of view of breast surgery, it is considered appreciable talk about aesthetic outcome.